El trabajo doméstico y de cuidado no remunerado en los países andinos - Cornejo Lobo, Rebeca Ivonne (2022)
In this article, the author analyzes the situation of unpaid domestic work and care work taking into consideration the results of the time use surveys carried out in the countries of the Andean Subregion and their contribution to GDP. Time use studies provide valuable information on how people allocate their time for paid and unpaid work, showing that there is an unequal distribution between women and men. Women work longer hours than men in Peru, Ecuador, Bolivia and Colombia, where data is available, regardless of their condition. On the other hand, it allows us to verify the importance of domestic work and unpaid care work in social reproduction.